DIALEKTIKA EPISTEMOLOGI NALAR ISLAM ABED AL-JABIRI DAN IMPLIKASINYA DALAM PENDIDIKAN ISLAM MODERN - Rohmadi Rohmadi; M. Afiqul Adib; M. Marjuki Duwila (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study aimsto explore the epistemological dialectic of Abed al-Jabiri's Islamic rationality andanalyze its implications in the context of modern Islamic education. Against the backdrop of the need for renewal in Islamic education that is capable of accommodatingthe changing times, this study focuses on Abed al-Jabiri's key conceptsand how his epistemology can shape relevant Islamic education. The research methodis qualitative, using a descriptive analytical approach.Data was collected through a literature study of Abed al-Jabiri's works that arerelevant to the epistemology of Islamic reasoning. Data analysis was carried out bydetailing and identifying the main concepts, as well as analyzing the implicationsof this epistemology in modern Islamic education. The findings of this researchare expected to provide deep insight into the thoughts of Abed al-Jabiri,while also opening up space for the development of Islamic education that is more adaptiveto the context of the times, namely combining Islamic values with the demands of themodern